Description of two new species of Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the Western Ghats of Kerala, India - Cyriac, Vivek Philip; Johny, Alex; Umesh, P. K.; Palot, Muhamed Jafer (Zootaxa, 2018)
Two new species of geckos of the genus Cnemaspis Strauch, 1887 are described from the southern Western Ghats of Kerala. Both species are medium to large sized Cnemaspis and can be differentiated from all other Indian congeners by a suite of distinct morphological characters. Both species are found in the high elevation forests of the two major massifs—       Anaimalai Hills and Agasthyamalai Hills and are presently known to have very restricted distributional ranges. The discovery of these novel species highlights the understudied diversity of reptiles in the high mountain ranges of the Western Ghats.